Determinantes para a prática de atividades físicas e esportivas adaptadas em indivíduos com lesão medular: um estudo retrospectivo de 20 anos - Cynthia Maris Lemes Ponzo Ribeiro (2022)
The spinal cord injury is considered one of the priorities for global health, not only due to the disability it causes but also for the expenses generated for the health systems. The adapted sport and the practice of physical activity may be indicated to improve the quality of life, promote social inclusion and contribute to the insertion of individuals with spinal cord injury in the sports world, however, some of these individuals have difficulties in staying active after the rehabilitation program. Thus, the purpose of this study was to investigate the determinants for the practice of adapted sports and physical activity in individuals with spinal cord injury. In total, the medical records of 1,806 adults with spinal cord injury were assessed. The selected medical records refer to individuals who experienced an adapted sports initiation program while they were hospitalized for a rehabilitation program at the SARAH Network of Rehabilitation Hospitals in Belo Horizonte, MG, Brazil, in the last 20 years. During the analysis of the medical records, a semi-structured form was filled out regarding personal and sociodemographic data, and information related to health history, sports modality practiced, time of sports practice, and presence of pain or associated pathologies. The median age of the individuals was 28 years (23-36), 86% were male and 67% were paraplegic. After the rehabilitation program, 55.8% of the individuals became physically active and 9.6% became athletes. The majority, (92.5%), practiced the physical activity or sport for more than 6 months. Female gender was associated with sedentarism (OR: 2.87, CI 1,07-7,73), A history of physical activity (OR:10.26, CI 1,30-80,83), and longer follow-up time of physically active individuals by the rehabilitation team (OR:0. 94, CI 0,84-0,97) increased the chances of the individual becoming an athlete. A lower number of modalities tried in hospitalization (OR:21.6, CI 3,12-150,71) and in the community (OR:5.07, CI 1,47-17,42) increased the chances of the individual developing a sedentary profile. Experiencing wheelchair basketball (OR:135, CI 50-362), wheelchair tennis (OR:108, CI 11-1035), swimming (OR:48, CI 26-88), wheelchair rugby (OR:37, CI 11-118), and table tennis (OR: 35, CI 21-352) increased the chances of the physically active individual developing the athlete profile. The increase in the age of individuals (OR:0.94, CI 0,90-0,98) and a longer time of follow-up by the rehabilitation team (OR:0.76, CI 0,652-0,88), reduced the chances of the individual abandoning the activity early. The number of sport modalities practiced during hospitalization (OR:3.84, CI 1,08-13,76) and the presence of pain in the thoracic (OR:19.67, CI 1,70-227) and lumbar (OR:29.41, CI 2,39-333) regions increase the chances of the individual to maintain the practice of physical activity or sport for a longer time. Based on these results, the determinants for the practice of physical activity or adapted sport were gender, history of physical activity, time of follow-up by the rehabilitation team, number of modalities tried during hospitalization and in the community, and community experience in the wheelchair basketball, wheelchair tennis, swimming, wheelchair rugby and table tennis modalities. In addition, age, length of follow-up by the rehabilitation team, number of modalities practiced during hospitalization, and presence of pain in the thoracic and lumbar regions influenced the time of maintenance of physical activity or adapted sport. Considering these aspects, the rehabilitation team will be able to identify potential athletes and physical activity practitioners, in order to better direct the guidelines for these individuals.